2019
DOI: 10.32098/mltj.04.2014.04
|View full text |Cite
|
Sign up to set email alerts
|

Exercise protocol induces muscle, tendon, and bone adaptations in the rat shoulder

Abstract: Exercise protocol induces muscle, tendon, and bone adaptations in the rat shoulder tendon collagen content, cross-sectional area, and mechanical properties were measured. Supraspinatus muscle cross-sectional area, weight, and the expression of mitochondrial oxidative phosphorylation (OXPHOS) proteins were measured. Humeri were analyzed with μCT and mechanically tested. Results: exercise decreased fat pad mass. Supraspinatus muscle hypertrophied and had increased OXPHOS proteins. Humerus trabecular bone had inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Most, but not all previous studies, 27 have detected adaptation of the humerus to treadmill exercise including increased bone mineral content, 46 bending strength, 47 and cortical bone thickness. 48 In conclusion, these studies are the first to show the potential role of plasma membrane disruptions as a mechanosensation mechanism in osteocytes. As PMD repair failure in skeletal muscle leads to myopathy, explaining loss of muscle strength in a variety of conditions including diabetes, 9,49,50 we anticipate that these results in bone may have direct physiological relevance for skeletal health; future studies will 660 YU ET AL.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Most, but not all previous studies, 27 have detected adaptation of the humerus to treadmill exercise including increased bone mineral content, 46 bending strength, 47 and cortical bone thickness. 48 In conclusion, these studies are the first to show the potential role of plasma membrane disruptions as a mechanosensation mechanism in osteocytes. As PMD repair failure in skeletal muscle leads to myopathy, explaining loss of muscle strength in a variety of conditions including diabetes, 9,49,50 we anticipate that these results in bone may have direct physiological relevance for skeletal health; future studies will 660 YU ET AL.…”
Section: Discussionmentioning
confidence: 74%
“…We observed osteocyte wounding in both the hindlimbs and forelimbs. Most, but not all previous studies, have detected adaptation of the humerus to treadmill exercise including increased bone mineral content, bending strength, and cortical bone thickness …”
Section: Discussionmentioning
confidence: 91%
“…During surgery when subscapularis tendon status allows, we repair the tendon with a tendon to tendon technique; this procedure can increase anterior stability of the implant in deltopectoral approach surgery by increasing the thickness of the soft tissue between the skin and prosthesis, according to some Authors but this issue deserve to be better studied in the future 3,4,25,27 . Vourazeris et al 27 and Clark et al 3 did not find a significant difference in dislocations and complication rate among patients with subscapularis repair and without, on the contrary, Edwards et al 25 concluded that all their patients with an implant dislocation did not undergo to a SSC tendon repair, but all of these had a complex shoulder pathology status, like proximal humeral nonunion, fixed glenohumeral dislocation, and failed prior arthroplasty. Nowadays, it depends largely on the implant lateralized designs that increases the lateral humeral and glenoid offsets and the deltoid provides the correct tension by increasing the compressive forces.…”
Section: Group a Group B Group Cmentioning
confidence: 97%
“…According to clinical diagnosis, radiographic preoperative data and intraoperative parameters that can lead to positive or negative results or facilitate the incidence of complications, we selected three groups of patients, dedicating each one a specific level of care, as follows 2,6,9,12,[15][16][17][18][19][20][21][22][23][24][25] . Group A (low care, n=52): diagnosis of Primary OA, CTA, massive rotator cuff tear, absence of hyperkyphosis or scapular dyskinesia, Glenoid assessment according to Walch 16 A1 or A2 and according to Favard 17 E0, E1 and E2, Infraspinatus and Teres minor fatty infiltration according to Goutallier 18,22 less than 3, no spine nonunion, not repaired SSC, no intraoperative complications or tendon transfers.…”
Section: Patients Groups Featuresmentioning
confidence: 99%
“…It is useful to do a pre and post-operative MRI evaluation, in order to ensure the correct placement of the anchors. It is also necessary to return as quickly as possible at sport activity through an intensive and specific rehabilitation 25,26 , performed several times during the day, based on sport-specific movements. In conclusion, according to our experience, arthroscopic surgical approach appears to be excellent in shoulder instability management, reducing recovery time, allowing a faster return to sport, with less pain, if compared with open surgery.…”
Section: Discussionmentioning
confidence: 99%